Study of the Beef Cattle Rearing System and Farmers’ Knowledge of Bovine Ephemeral Fever (BEF) in the Kalipuro District, Banyuwangi Regency - Aini Mardhiah; Bodhi Agustono; SunaryoHadi Warsito; Maya NurwartantiYunita; Widya Paramita Lokapirnasari; RagilAngga Prastiya; Faisal Fikri; Shekhar Chhetri; SarasatiWindria (The Indian Veterinary Journal, 2023)
This study aims to determine the relationship between beef cattle husbandry systems and farmer understanding based on gender, age, last education, type of work, and number of farm animals and the incidence of Bovine Epstein-Barr Virus (BEF). This study was conducted using two methods: interviews and the completion of questionnaires. The sample or respondents chosen for this study consisted of one hundred beef cattle producers. Before disseminating the questionnaires to the respondents, their validity and dependability were evaluated to ensure they met the criteria for a data measurement instrument. 59% of farmers did not comprehend the incidence of BEF, 22% understood, and 19% understood very well, based on the characteristics of the respondents. The analysis of the correlation between the rearing system and the level of understanding of farmers on the incidence of Bovine Ephemeral Fever (BEF) disease yielded a significant p value level of p<0.05, indicating that there was a correlation between the beef cattle rearing system and the level of understanding of farmers based on sex, age, last education, breed, occupation, and the number of pets owned by farmers.